Tourism-led Urban Regeneration - Mendes, Luís (2022)
Tourism has proved to be a critical and successful factor in triggering urban regeneration as a proactive response to specific urban problems. Tourism-led urban regeneration introduces new urban policies that seek to revitalize the urban space, mobilizing the territorial benefits of tourism development to enhance the socioeconomic, morphological, environmental and functional values of certain urban areas. It is implemented by developing multiple intervention strategies, orchestrating a set of coherent and programmed actions with the purpose of substantially raising the quality of life of resident populations. Urban regeneration also creates lasting improvements in the built environment, qualifying the assets and resources of the city itself as a tourist destination (Özden and Turgut, 2005).